The role of protected areas in the conservation of the Curly Birch gene pool - Lidiya Vetchinnikova; Alexander Titov (Proceedings of the Karelian Research Centre of the Russian Academy of Sciences, 2018)
The article is devoted to the problem of conservation of the curly (Karelian) birch and the role of protected areas (PAs) in this effort. Data on curly birch numbers and distribution across PAs of various categories in the Republic of Karelia are reported. In view of its limited resources, curly birch has been recognized as a specially protected variety since the very beginning of its systematic studies (early 1930’s). The history of establishment of the network of PAs featuring curly birch is briefly described, and their current state is assessed. It is shown that in spite of the lack of actual control and tending in the PAs, on the whole they have secured the preservation of more than 90 % of the regionally red-listed curly birch resources. All natural curly birch populations are concentrated within four botanical reserves (“Anisimovschina”, “Spasogubsky”, “Kakorovsky” and “Karelian birch near the village of Tsarevichi”), which collectively occupy no more than 0.01 % of the total area of protected areas. The main reasons for the sharp reduction of curly birch resources, as well as the negative consequences associated with its decline are discussed. Using microsatellite markers, it was shown that a decrease in the total and effective population of the curly birch caused by its prolonged exploitation (including illegal logging) has led to a change in its genetic structure and increased inbreeding. The observed processes have resulted in a decline of the genetic diversity and depletion of the gene pool of the curly birch, as well as a nearly total absence of its viable undergrowth. Nevertheless, PAs established in Karelia have played and continue to play an important role in preserving the gene pool of the curly birch, and its elite trees remain the main target for various scientific studies and practical work for the reproduction and re-introduction of the curly birch.